Public Information Precision and Borrower Risk-Taking Implications for Financial Reporting Regulations - Rizal, Muhammad; Kusnanto, Eri (International Journal of Management, Accounting & Finance (KBIJMAF), 2024)
This research explores the relationship between public information precision, borrower risk-taking behavior, and financial reporting regulations. It examines how varying levels of accounting disclosures influence creditor-borrower dynamics in financial markets. Enhanced precision in public information, such as accounting earnings, promotes market efficiency by reducing information asymmetry and improving creditors' ability to accurately assess borrower creditworthiness. While higher precision generally mitigates borrower risk-shifting tendencies, regulatory context and economic conditions modulate these effects. This literature review systematically identifies and analyzes peer-reviewed articles on forecast dispersion, accuracy, and their implications for cross-sectional return anomalies in financial markets. The findings reveal that higher forecast dispersion is linked to greater uncertainty and perceived risk, leading to higher expected returns, while accurate forecasts reduce information asymmetry and improve market efficiency. Differences in forecast precision significantly contribute to market anomalies. In conclusion, forecast dispersion and accuracy are critical in explaining cross-sectional return anomalies. Future research should refine models, explore behavioral biases, and evaluate technological advancements, emphasizing balanced financial reporting regulations to harness transparency benefits while mitigating potential costs during economic expansions.